Avaliação das ectonucleotidases como biomarcadores na progressão do câncer de próstata - Gardani, Carla Fernanda Furtado (2018)
Prostate cancer (PC) is the second most diagnosed neoplasm in men, with the exception of non- melanocytic skin tumors. Its global incidence is 1.1 million cases per year and its mortality rate is around 307,000 deaths. Around the world, there are 3,850,000 CP survivors, since their survival in five years reaches values exceeding 80%. Therefore, adequate stratification in the diagnosis and follow-up of these patients is so relevant. In this study, we aimed of evaluating ATP / ADP / AMP hydrolysis as a prognostic biomarker in the CP; CD39 and CD73 enzymes are known to be responsible for the transformation of ATP or ADP into AMP and into adenosine, respectively. Blood samples were collected from 29 patients treated at the Cruz Alta Oncology and Hematology Center (COHCA) and 17 healthy controls (CS), in order to evaluate the hydrolysis activity of ATP, ADP and AMP and to correlate the data between the cases and controls. In addition, the results of hydrolysis were correlated with recognized prognostic factors as Gleason Score (EG), clinical stage (EC) and PSA levels. The mean age of the selected patients was 63.3 years, 71.4% presented PSA <10 at diagnosis, 82.7% were grouped as low in EG and 48.3% of patients belonged to EC IIB. The results demonstrated statistically significant differences in the nucleotide hydrolysis profiles of the cases and controls. In the CP patients the AMP hydrolysis was higher when compared to the hydrolysis of ATP and ADP. Regarding the clinical staging, it was observed that the hydrolysis of ATP was higher in the initial clinical stages, whereas the AMPase remained high regardless of clinical stage. Therefore, we can conclude that the understanding of the ectonucleotidases activities and their influence on tumor progression can collaborate for the diagnostic and improve the therapeutic approach for this neoplasia.